Student Engagement, Life Satisfaction, and Academic Burnout Among Polish Tertiary Students: A Mixed-Methods Analysis - Arkadiusz Pietluch; Magdalena Trinder; Marta Dick-Bursztyn (Multidisciplinary Journal of School Education)
Objective of the study: Given the scarcity of research in this area, the present study was carried out to examine the relationship between student engagement, life satisfaction, and academic burnout in the Polish academic setting. Additionally, a qualitative analysis was conducted to explore the factors that sustain student engagement.